Human Vital Physiological Parameters Monitoring: A Wireless Body Area Technology Based Internet of Things - Aliyu Ahmed; Ajao Adewale Lukman; Agajo James; Olaniy Olayemi Mikail; Buhari Ugbede Umar; Emmanuel Samuel (Jurnal Teknologi dan Sistem Komputer, 2018)
Human vital physiological parameters (HVPP) monitoring with embedded sensors integration has improved the smart system technology in this era of a ubiquitous platform. Several IoT-based healthcare applications have been proposed for remote health monitoring. Most of the devices developed require one on one contact with doctors before any medical diagnosis is undertaken. Thereby, make it difficult for frequent visitation to the health center. In this paper, embedded heartbeat and temperature sensors for remote monitoring have been developed using Arduino lily as the system controller and processing unit. The Bluetooth low power enables with Android mobile apps is used for remote monitoring and communication of HVPP in a real time. This gives medical personnel and individual customers opportunity of monitoring their vital physiological parameters such as heartbeat rate and body temperature. However, it moderates sudden attack of chronic ailment like hypertension and reduces congestion of patient in the hospitals.